Records management at the Council of Europe (2): the digital turn. Issue 2 (1st August 2021) - Büttner, Gesa
Abstract : The implementation of electronic records management at the Council of Europe was a crucial step in leading the intergovernmental human rights organization towards comprehensive corporate information management. The motivation for introducing records management was to improve access to information. Finding information proved to be difficult due to the fragmented information landscape, combined with a lack of governance for digital information. To amend this situation, corporate control and standardization were introduced along the whole information life cycle, involving the information producers as key players. The article describes this implementation, covering roughly the decade from 2008 to 2018, from its foundations and preparations to the deployment, awareness-raising and training activities. Special emphasis is put on the instruments that support a standardized records management approach, such as business classification scheme, retention and disposal schedules, and metadata. The success and failure points are briefly presented. It appears that records management can be a catalyst for corporate-wide information management.